Versatile solid modifications of icariin: structure, properties and form transformation. Issue 39 (17th September 2015) - Jia, Lina; Zhang, Qi; Wang, Jian-Rong; Mei, Xuefeng
Abstract : Two new polymorphs and ten different solvates were obtained. The isostructural phenomenon was readily observed among various organic solvates. The single crystal structure of the marketed hydrate form H1 was determined for the first time through a single crystal-single crystal transformations (SCSCTs) process. Abstract : A comprehensive solid-state screening experiment was performed for icariin (ICA), an active substance in Traditional Chinese Medicine (TCM) which has long been used to treat osteroporosis. Two new polymorphs in their pure forms and ten different solvate modifications were obtained and the single crystal structures were successfully determined. The isostructural phenomenon was readily observed among various organic solvates. Notably, the single crystal structure of the marketed hydrate form H1 was determined for the first time through a single crystal–single crystal transformation (SCSCT) process. The physicochemical properties of various solid forms were further studied. The results show that the newly discovered pure form α presents better thermal stability, lower hygroscopicity and higher solubility compared to the currently marketed form. The superior physicochemical properties render a better drug development ability for this widely applied TCM.